Association of neopterin as a marker of immune system activation and juvenile rheumatoid arthritis activity - Mones M. Abu Shady; Hanan A. Fathy; Alaa Ali; Eman R. Youness; Gihan A. Fathy (Brazilian Society of Pediatrics, 2015)
Objective: To evaluate neopterin plasma concentrations in patients with active juvenile idiopathic arthritis (JIA) and correlate them with disease activity. Methods: Sixty patients diagnosed as active JIA, as well as another 60 apparently healthy age‐ and gender‐matched children as controls, were recruited from the Pediatrics Allergy and Immunology Clinic, Ain Shams University. Disease activity was assessed by the Juvenile Arthritis Disease Activity Score 27 (JADAS‐27). Laboratory investigations were performed for all patients, including determination of hemoglobin concentration (Hgb), erythrocyte sedimentation rate (ESR), and C‐reactive protein. Serum concentrations of tumor necrosis factor‐alpha (TNF‐α), interleukin‐6 (IL‐6), monocyte chemoattractant protein‐1 (MCP‐1), and neopterin were measured. Results: Significant differences were found between JIA patients and controls with regard to the mean levels of Hgb, ESR, TNF‐α, IL‐6, and MCP‐1 (p < 0.05). A statistically significant higher mean level serum neopterin concentration (p < 0.05) was found in JIA patients (20.43 ± 8.73 nmol/L) than in controls (6.88 ± 2.87 nmol/L) (p < 0.05). Positive significant correlations were detected between serum neopterin and ESR, TNF‐α, IL‐6, MCP‐1, and JADAS‐27 (p < 0.05). No correlation was found between serum neopterin and CRP (p > 0.05). Multiple linear regression analysis showed that JADAS‐ 27 and ESR were the main variables associated with serum neopterin in JIA patients (p < 0.05). Conclusion: The elevation of plasma neopterin concentrations in early JIA patients may indicate stimulation of immune response. Serum neopterin can be used as a sensitive marker for assaying background inflammation and disease activity score in JIA patients.